The nutritional status of pregnant women in relation to alcohol consumption during pregnancy, and pregnancy outcome - Klinger, Ingrid (Stellenbosch : University of Stellenbosch, 2011)
Thesis (MVoeding)--University of Stellenbosch, 2004.